Valorization alternatives of colombian bee-pollen for its use as food resource - a structured review - ZULUAGA DOMÍNGUEZ, Carlos Mario; SERRATO BERMUDEZ, Juan Carlos; QUICAZÁN de C., Martha Cecilia (Vitae, 2014)
Background: Pollen of honey-bee Apis mellifera L. is a product gathered for human consumption and marketed as a nutritional and functional resource. However, some studies indicate that it is necessary to develop transformation processes to modify the external structure of pollen, which is extremely difficult and prevents the nutrients and bioactive compounds to be completely digested in the gastrointestinal tract. The bee-pollen productivity in Colombia is up to five times higher than in countries traditionally recognized for its marketing, making this a valuable business opportunity. Objectives: To describe the chemical structure and the most important nutritional and functional components in bee pollen, as well as to understand the availability of compounds and some backgrounds reported for the opening of the bee-pollen grain, both in a natural and artificial manner. Methods: The literature search involved the use of different terms, alone or combined, by using logical operators; some terms were: pollen, beebread, bioactive and nutritional compounds, bioavailability, pollen structure, exine, fertilization. Selected search fields were the title or abstract of the publication in the following databases: Directory of Open Access Journals, Emerald, Pubmed, Redalyc, Scientific Electronic Library Online, Science Direct, Springer Journal, Taylor & Francis, Wiley Online Library. The selected literature was that found mainly between 2008 and 2014in Spanish and English. Results: The nutritional and functional composition of bee-pollen is widely reported; nevertheless, few studies on transformation processes to improve the availability of the compounds present in this product were found. The natural fermentation process occurred within the hive to obtain the product known as “bee-bread” is highlighted, since an emulation of this transformation could be developed in a controlled manner for a scaled production; despite this, further research in the involved biotechnological aspects is still required. Conclusions: Efforts have been made to characterize the bee-pollen from a physical-chemical point of view, but no significant progress in the development of processes of transformation has been reached. The future trends should aim at developing engineering processes emulating the phenomena occurred in nature where structural changes in the outer layer of bee-pollen can be achieved.